Integration of Islamic Education with Science in the National Education System - Arifuddin Jalil; Alpizal; Abu Bakar (Journal of Practice Learning and Educational Development, 2025)
Integrating Islamic education with science is a strategic approach to building a holistic and transformative education system. In the Islamic scholarly tradition, there is no dichotomy between religious and scientific knowledge; both are seen as complementary manifestations of God's revelation and creation. This research aims to examine the concept, urgency, strategies, and challenges of integrating Islamic education and science within the context of Indonesia's national education system. A qualitative-descriptive approach was used, with literature studies and empirical reviews as the primary methods. The study results indicate that integration can be achieved thru the development of an integrative curriculum, teacher capacity building, the establishment of model educational institutions, and the strengthening of monotheistic values in character education. A case study of Madrasah Aliyah Program Khusus (MAPK) shows that integration is not only theoretically possible but can also be practically implemented with the right policy support and academic culture. This research recommends the need for structural policies and systemic support in developing an integrative education model to produce a generation of knowledgeable and virtuous Muslims.